Low-stand lakes and garbled gastropods: the problems of interpreting the enigmatic deglacial and postglacial environments of the Celtic Sea Shelf - Furze, Mark F.A. (My University, 2012)
Recent work on the last glaciation of the British Isles has lead to an improved understanding of the nature and timing of the retreat of the British-Irish Ice sheet (BIIS) from its southern maximum (Isles of Scilly).